SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL FLIPPED CLASSROOM BERBANTUAN MEDIA DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Mayyadah, Umi; Nindiasari, Hepsi; Khaerunnisa, Etika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Flipped Classroom model assisted by digital media on students' mathematical critical thinking skills. The method used was a Systematic Literature Review (SLR) referring to the PRISMA stages, including identification, screening, eligibility, and article inclusion. From 46 articles accredited in SINTA 4 to SINTA 1 and Scopus published between 2016 and 2025, 20 articles met the inclusion criteria and were analyzed descriptively and qualitatively with research subjects consisting of elementary, junior high school, senior high school students, and university students. The results of the review indicate that the implementation of the Flipped Classroom model assisted by digital media has a positive effect on students' mathematical critical thinking skills and also improves conceptual understanding, problem-solving skills, active engagement, and learning independence. Digital media such as learning videos and e-learning platforms help students study materials independently, making classroom learning processes more effective. Therefore, the Flipped Classroom model assisted by digital media can be an effective learning alternative in supporting the development of students' mathematical critical thinking skills, although its effectiveness is influenced by instructional design, technological readiness, and teacher competence.